Preparation method of CA-MIL-88A (Fe) loaded active carbon fiber composite material

By loading CA-MIL-88A (Fe) on activated carbon fiber in situ growth method to form activated carbon fiber composites, the problems of limited photocatalytic activity of Fe-MOFs catalysts and easy agglomeration of powdered catalysts are solved, and efficient adsorption and degradation of dyes are achieved, achieving the purpose of saving water and reducing pollutant emissions.

CN119633749APending Publication Date: 2025-03-18NANTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822090.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing Fe-MOFs catalysts are limited in terms of photocatalytic activity, and powdered catalysts are prone to agglomeration and difficult to recover, which limits their commercial applications.

Method used

The activated carbon fiber is loaded with CA-MIL-88A(Fe) by in-situ growth method to form an activated carbon fiber composite material loaded with CA-MIL-88A(Fe), which utilizes its excellent adsorption and photocatalytic properties.

Benefits of technology

It effectively adsorbs and degrades dyes in wastewater that are not easily degraded under sunlight, solves the color problem caused by water reuse during printing and dyeing or water-soluble dyes in wastewater, and achieves the purpose of saving water and reducing pollutant emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633749A_ABST
    Figure CN119633749A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon fiber composite materials, in particular to a preparation method of a CA-MIL-88A (Fe)-loaded active carbon fiber composite material, which comprises the following steps: firstly, pretreating active carbon fibers with nitric acid, and then preparing the CA-MIL-88A (Fe)-loaded active carbon fiber composite material by taking ferric chloride as a metal salt and fumaric acid FA and citric acid CA as ligands. CA-MIL-88A (Fe) is loaded on the pretreated active carbon fiber by adopting an in-situ growth method, so that the active carbon fiber composite material loaded with the CA-MIL-88A (Fe) can be prepared. The CA-MIL-88A (Fe) which is large in specific surface area and high in light absorption capacity is loaded on the modified active carbon fiber material in situ to prepare the reusable composite material with the efficient decolorization performance, the method is simple in process, the excellent performance of the active carbon fiber and the adsorption performance and photocatalytic performance of the CA-MIL-88A (Fe) on dye are fully utilized, and the composite material is suitable for industrial production. The composite material can effectively adsorb and degrade dyes which are not easy to degrade in wastewater under the irradiation of sunlight, so that the problem of chromaticity caused by water reuse of printing and dyeing reclaimed water or water-soluble dyes in wastewater is solved, and the purposes of saving water and reducing pollutant discharge are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber composite materials, and in particular to a method for preparing an activated carbon fiber composite material loaded with CA-MIL-88A (Fe). Background Art

[0002] Iron-based metal-organic framework materials (Fe-MOFs) have catalytic abilities similar to Fenton catalysts due to the presence of Fe-O bonds in their structures. They are also rich in iron, cheap and easily available, and environmentally friendly. They are considered to be the most suitable MOFs for wastewater treatment. There are many types of Fe-MOFs. The most classic Lavoisier (Materials also of Institute Lavoisier, MILs) series include MIL-53 (Fe), MIL-88A (Fe), MIL-88B (Fe), MIL-100 (Fe) and MIL-101 (Fe). Among them, MIL-88A (Fe) is a porous material synthesized from Fe (III) and fumaric acid. Compared with other MOFs, MIL-88A (Fe) synthesized with deionized water has a reversible swelling effect while completely maintaining its open skeleton topology, which makes it easier for reactants to adsorb to the active sites, which is beneficial to the mass transfer of the catalytic reaction. Therefore, MIL-88A(Fe) has attracted extensive attention due to its unique properties in adsorption, catalytic degradation, separation, chemical sensors, etc. However, when MIL-88A(Fe) is used as a catalyst alone, its electron-hole recombination is easy and its catalytic activity is limited. In addition, powder catalysts have problems such as easy agglomeration and difficulty in recycling and reuse, which greatly limits their commercial application.

[0003] In addition to external factors such as light intensity, solution pH, ambient temperature, catalyst dosage and pollutant concentration, the factors that affect photocatalytic activity are closely related to the crystal structure, specific surface area, band gap width, catalyst utilization rate, separation and recombination of photogenerated carriers, etc. of the catalyst itself. One of the effective methods to improve the photocatalytic activity of MOFs is to use mixed organic ligands to increase its specific surface area to improve its light absorption capacity. WANG Yuexin et al. introduced more monodentate ligands into NH2-MIL-88B(Fe) through pyrrole-2-carboxylic acid and generated more ligand vacancies, which improved light absorption, charge separation and Fe 2+ / Fe 3+Redox reaction, which is beneficial to the photo-Fenton degradation of acetamiprid. TANChungen et al. used two organic ligands, 2-methylimidazole and fumaric acid, to prepare a mixed organic ligand MIL-88A. The prepared MIL-88A has the characteristics of small particle size and high oxidation potential, and has a high removal rate for azo dyes. Some researchers have combined MIL-88A with other materials such as g-C3N4, γ-Fe2O3, ZnIn2S4, etc. to prepare composite materials for photocatalytic heavy metal reduction, decomposition of organic pollutants and production of hydrogen. The synergistic effect of different materials makes the MIL-88A composite material have significant photocatalytic performance. However, the complex preparation process and high cost of these composite materials limit the practical application of composite materials.

[0004] Activated carbon fiber has a large specific surface area, excellent chemical stability and conductivity, and is often used as an adsorbent or catalyst carrier, and is widely used in wastewater treatment. Loading MOFs on activated carbon fiber can effectively solve the problem that powdered MOFs are easy to agglomerate and difficult to recycle during use. The inventor's research group has previously prepared a series of fiber-based Fe-MOFs composite materials for photocatalytic decolorization of dyes, and found that the decolorization effects of the composite materials on different dyes vary greatly. Wang Jing et al. prepared TiO2 / MIL-100(Fe) / PA composite materials using an in-situ growth method. The decolorization rates of different dyes are from high to low, namely, reactive black KN-B, reactive brilliant red M-3BE, and reactive brilliant blue KN-R, among which the decolorization rate of reactive brilliant blue KN-R is only about 63%. Fan Tingting et al. prepared acrylic-based MIL-100 (Fe) composite materials using the in-situ growth method. The decolorization rates of different dyes are as follows: reactive black KN-B, rhodamine B, reactive brilliant red M-3BE, and reactive brilliant blue KN-R, from high to low. The decolorization rate of reactive brilliant blue KN-R is only about 55%. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings existing in the prior art, and to propose a preparation method of an activated carbon fiber composite material loaded with CA-MIL-88A (Fe). The composite material makes full use of the excellent properties of the activated carbon fiber and the adsorption and photocatalytic properties of CA-MIL-88A (Fe) for dyes, so that the composite material can effectively adsorb and degrade the dyes that are not easily degraded in wastewater under sunlight, so as to solve the chromaticity problem caused by the reuse of printing and dyeing water or the water-soluble dyes in wastewater, thereby achieving the purpose of saving water and reducing pollutant emissions.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing an activated carbon fiber composite material loaded with CA-MIL-88A(Fe), comprising the steps of pretreating the activated carbon fiber with nitric acid, and then loading CA-MIL-88A(Fe) on the pretreated activated carbon fiber by an in-situ growth method using ferric chloride as a metal salt, fumaric acid (FA) and citric acid (CA) as ligands, thereby obtaining the activated carbon fiber composite material loaded with CA-MIL-88A(Fe).

[0008] Preferably, the activated carbon fiber pretreatment is to add the activated carbon fiber into a 10% nitric acid solution at a bath ratio of 1:50, immerse it at 70°C for 4 hours, take it out, wash it with deionized water until it is neutral, and dry it in a 100°C oven.

[0009] Preferably, the in-situ growth method is to immerse 10 to 20 g / L of pretreated activated carbon fiber in a mixed ligand solution composed of CA and FA, and then oscillate it in a water bath oscillator at 60°C for 1 hour. Then, an equal volume of ferric chloride solution is added to the mixed ligand solution soaked with activated carbon fiber, and the oscillation treatment is continued for 6 hours. After the reaction is completed, the sample is washed 3 times with deionized water and ethanol respectively, and dried.

[0010] Preferably, the concentration of the mixed ligand solution composed of FA and CA is 80-100 mmol / L, and the molar ratio of FA to CA is 6:1-8:1.

[0011] Preferably, the concentration of the ferric chloride solution is 80-100 mmol / L.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] 1. The present invention prepares a reusable composite material with high-efficiency decolorization performance by in-situ loading CA-MIL-88A (Fe) with large specific surface area and strong light absorption capacity onto modified activated carbon fiber materials. The method has a simple process and makes full use of the excellent performance of activated carbon fiber and the adsorption and photocatalytic properties of CA-MIL-88A (Fe) for dyes, so that the composite material can effectively adsorb and degrade the dyes that are not easily degraded in wastewater under sunlight, so as to solve the chromaticity problem caused by the reuse of printing and dyeing water or water-soluble dyes in wastewater, thereby achieving the purpose of saving water and reducing pollutant emissions.

[0014] 2. The composite material prepared by the present invention has both efficient decolorization effect and is easy to reuse, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a diagram showing the effect of decolorizing reactive brilliant blue KN-R dye by the samples of Examples 1, 2 and 3 of the present invention. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0017] Example 1

[0018] A method for preparing a CA-MIL-88A (Fe) loaded activated carbon fiber composite material, the specific steps are as follows:

[0019] The activated carbon fibers were added into a 10% nitric acid solution at a bath ratio of 1:50, immersed at 70°C for 4 hours, taken out, washed with deionized water until neutral, and dried in an oven at 100°C.

[0020] Weigh a certain amount of FA, add deionized water and heat to dissolve, add CA at a molar ratio of FA to CA of 6:1, and prepare a mixed ligand solution with a concentration of 80mmol / L. Weigh a certain amount of ferric chloride hexahydrate, dissolve it in deionized water and prepare an iron salt solution with a concentration of 80mmol / L. Take a certain amount of pretreated activated carbon fiber, add it to the mixed ligand solution at a solid-liquid ratio of 1:50, oscillate in a water bath oscillator at 60°C for 1h, add an equal volume of iron salt solution to the mixed ligand solution soaked with activated carbon fiber, and continue to oscillate for 6h. After the reaction is completed, the sample is washed 3 times with deionized water and ethanol respectively, and dried to obtain an activated carbon fiber composite material loaded with CA-MIL-88A (Fe).

[0021] In order to investigate the decolorization effect of the prepared composite material on organic dyes, the reactive brilliant blue KN-R dye was used as the decolorization object, and the decolorization performance of the composite material on the dye was determined. Test method: 0.1g of the composite material was placed in 50mL of 80mg / L reactive brilliant blue KN-R dye solution, 0.24mL / L of 30% H2O2 was added, and photocatalytic degradation was carried out under the irradiation of a 1000W xenon lamp for 60min. Every 10min, 3mL of the dye solution was removed to determine its absorbance, and the dye solution was returned after each test. The decolorization rate of the dye was measured. Figure 1 The decolorization rate of the dye after repeated use for 5 times is shown in Table 1.

[0022] Example 2

[0023] A method for preparing a CA-MIL-88A (Fe) loaded activated carbon fiber composite material, the specific steps are as follows:

[0024] The activated carbon fibers were added into a 10% nitric acid solution at a bath ratio of 1:50, immersed at 70°C for 4 hours, taken out, washed with deionized water until neutral, and dried in an oven at 100°C.

[0025] Weigh a certain amount of FA, add deionized water and heat to dissolve, add CA at a molar ratio of FA to CA of 7:1, and prepare a mixed ligand solution with a concentration of 90mmol / L. Weigh a certain amount of ferric chloride hexahydrate, dissolve it in deionized water and prepare an iron salt solution with a concentration of 90mmol / L. Take a certain amount of pretreated activated carbon fiber, add it to the mixed ligand solution at a solid-liquid ratio of 1:50, oscillate in a water bath oscillator at 60°C for 1h, add an equal volume of iron salt solution to the mixed ligand solution soaked with activated carbon fiber, and continue to oscillate for 6h. After the reaction is completed, the sample is washed 3 times with deionized water and ethanol respectively, and dried to obtain an activated carbon fiber composite loaded with CA-MIL-88A (Fe).

[0026] In order to investigate the decolorization effect of the prepared composite material on organic dyes, the reactive brilliant blue KN-R dye was used as the decolorization object, and the decolorization performance of the composite material on the dye was determined. Test method: 0.1g of the composite material was placed in 50mL of 80mg / L reactive brilliant blue KN-R dye solution, 0.24mL / L of 30% H2O2 was added, and photocatalytic degradation was carried out under the irradiation of a 1000W xenon lamp for 60min. Every 10min, 3mL of the dye solution was removed to determine its absorbance, and the dye solution was returned after each test. The decolorization rate of the dye was measured. Figure 1 The decolorization rate of the dye after repeated use for 5 times is shown in Table 1.

[0027] Example 3

[0028] A method for preparing a CA-MIL-88A (Fe) loaded activated carbon fiber composite material, the specific steps are as follows:

[0029] The activated carbon fibers were added into a 10% nitric acid solution at a bath ratio of 1:50, immersed at 70°C for 4 hours, taken out, washed with deionized water until neutral, and dried in an oven at 100°C.

[0030] Weigh a certain amount of FA, add deionized water and heat to dissolve, add CA at a molar ratio of FA to CA of 8:1, and prepare a mixed ligand solution with a concentration of 100mmol / L. Weigh a certain amount of ferric chloride hexahydrate, dissolve it in deionized water and prepare an iron salt solution with a concentration of 100mmol / L. Take a certain amount of pretreated activated carbon fiber, add it to the mixed ligand solution at a solid-liquid ratio of 1:50, oscillate in a water bath oscillator at 60℃ for 1h, add an equal volume of iron salt solution to the mixed ligand solution soaked with activated carbon fiber, and continue to oscillate for 6h. After the reaction is completed, the sample is washed 3 times with deionized water and ethanol respectively, and dried to obtain an activated carbon fiber composite material loaded with CA-MIL-88A (Fe).

[0031] In order to investigate the decolorization effect of the prepared composite material on organic dyes, the reactive brilliant blue KN-R dye was used as the decolorization object, and the decolorization performance of the composite material on the dye was determined. Test method: 0.1g of the composite material was placed in 50mL of 80mg / L reactive brilliant blue KN-R dye solution, 0.24mL / L of 30% H2O2 was added, and photocatalytic degradation was carried out under the irradiation of a 1000W xenon lamp for 60min. Every 10min, 3mL of the dye solution was removed to determine its absorbance, and the dye solution was returned after each test. The decolorization rate of the dye was measured. Figure 1 The decolorization rate of the dye after repeated use for 5 times is shown in Table 1.

[0032] Table 1 Decolorization rate of repeated use of example samples

[0033] Number of times of reuse 1 2 3 4 5 Activated Carbon Fiber 22.9 3.2 2.5 2.1 1.8 Example 1 Sample 93.6 90.6 86.8 83.4 80.2 Example 2 Sample 98.7 92.3 88.4 85.1 82.4 Example 3 Sample 97.1 91.6 87.3 84.6 81.8

[0034] In summary, the preparation method of the present invention has a simple process and makes full use of the excellent performance of activated carbon fiber and the adsorption and photocatalytic properties of CA-MIL-88A (Fe) for dyes, so that the composite material can effectively adsorb and degrade the dyes that are not easily degraded in wastewater under sunlight, so as to solve the chromaticity problem caused by water reuse in printing and dyeing or water-soluble dyes in wastewater, thereby achieving the purpose of saving water and reducing pollutant emissions.

[0035] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an activated carbon fiber composite material loaded with CA-MIL-88A (Fe), characterized in that: The activated carbon fiber is first pretreated with nitric acid, and then CA-MIL-88A(Fe) is loaded on the pretreated activated carbon fiber by an in-situ growth method using ferric chloride as metal salt, fumaric acid FA and citric acid CA as ligands, thereby obtaining an activated carbon fiber composite material loaded with CA-MIL-88A(Fe).

2. The method for preparing a CA-MIL-88A(Fe) loaded activated carbon fiber composite material according to claim 1, characterized in that: The activated carbon fiber pretreatment is to add the activated carbon fiber into a 10% nitric acid solution at a bath ratio of 1:50, immerse it at 70°C for 4 hours, take it out, wash it with deionized water until it is neutral, and place it in a 100°C oven for drying.

3. The method for preparing a CA-MIL-88A (Fe) loaded activated carbon fiber composite material according to claim 1, characterized in that: The in-situ growth method is to immerse 10-20 g / L pretreated activated carbon fiber in a mixed ligand solution composed of CA and FA, and then oscillate it in a water bath oscillator at 60° C. for 1 hour. Then, an equal volume of ferric chloride solution is added to the mixed ligand solution soaked with the activated carbon fiber, and the oscillation treatment is continued for 6 hours. After the reaction is completed, the sample is washed 3 times with deionized water and ethanol respectively, and dried.

4. The method for preparing a CA-MIL-88A(Fe) loaded activated carbon fiber composite material according to claim 3, characterized in that: The concentration of the mixed ligand solution composed of FA and CA is 80-100 mmol / L, and the molar ratio of FA to CA is 6:1-8:

1.

5. The method for preparing a CA-MIL-88A(Fe) loaded activated carbon fiber composite material according to claim 3, characterized in that: The concentration of the ferric chloride solution is 80-100 mmol / L.